PENGARUH RASIO SOLVABILITAS TERHADAP HARGA SAHAM PADA INDUSTRI FOOD AND BEVERAGE DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Zuvilla, Telly; Setiawan, Arie Agus; Irawan, Anja (LP2M Politeknik Jambi, 2025)
This study aims to analyze the effect of solvency ratios on stock prices in the food and beverage sector companies listed on the Indonesia Stock Exchange during the period 2009–2013. The solvency ratios used include Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Long Term Debt to Equity Ratio (LTDER), and Current Liabilities to Net Worth (CLNW). The method employed is multiple linear regression with panel data. The results indicate that solvency ratios simultaneously have a significant influence on stock prices. However, partially, only LTDER shows a significant effect on stock prices, while DAR, DER, and CLNW do not. These findings imply that long-term debt structure plays an important role in shaping investor perceptions of company stock valuation.